Climate Change Mitigation: How Effective Is Green Quantitative Easing? - Raphael Abiry; Marien Ferdinandusse; Alexander Ludwig; Carolin Nerlich (Center for Economic Studies and ifo Institute (CESifo), 2022)
We develop a two sector incomplete markets integrated assessment model to analyse the effectiveness of green quantitative easing (QE) in complementing fiscal policies for climate change mitigation. We model green QE through an outstanding stock of private assets held by a monetary authority and its portfolio allocation between a clean and a dirty sector of production. Green QE leads to a partial crowding out of private capital in the green sector and to a modest reduction of the global temperature by 0.04 degrees of Celsius until 2100. A moderate global carbon tax of 50 USD is 4 times more effective.
Keywords: E51; E62; Q54; 330; climate change; integrated assessment model; 2-sector model; green quantitative easing; carbon taxation